Radio-quiet Gamma-ray Pulsars - Lupin Chun-Che Lin (Journal of Astronomy and Space Sciences, 2016)
A radio-quiet γ-ray pulsar is a neutron star that has significant γ-ray pulsation but without observed radio emission or only limited emission detected by high sensitivity radio surveys. The launch of the Fermi spacecraft in 2008 opened a new epoch to study the population of these pulsars. In the 2nd Fermi Large Area Telescope catalog of γ-ray pulsars, there are 35 (30 % of the 117 pulsars in the catalog) known samples classified as radio-quiet γ-ray pulsars with radio flux density (S1400) of less than 30 μJy. Accompanying the observations obtained in various wavelengths, astronomers not only have the opportunity to study the emitting nature of radio-quiet γ-ray pulsars but also have proposed different models to explain their radiation mechanism. This article will review the history of the discovery, the emission properties, and the previous efforts to study pulsars in this population. Some particular cases known as Geminga-like pulsars (e.g., PSR J0633+1746, PSR J0007+7303, PSR J2021+4026, and so on) are also to specified discuss their common and specific features.